Existing Eurocodes Applied to a Membrane Structure. (2016) - Pyl, Lincy; Wang, Xiduo; De Smedt, Elien; Colliers, Jimmy; Mollaert, Marijke; De Laet, Lars
Abstract: This article tries gaining insight in the effect of the partial factor starting by the analysis of a steel cable net structure according to Eurocode 3. Eurocode specifies a value of 1.35 for the partial factor for prestress. A cable net structure built in 1958, was used as a case study. In spite of the lack of design guidelines and calculation tools 58 years ago, the analysis according to the current design standard Eurocode 3 for steel shows that the results match quite well with the original calculation. Generally speaking, a reduction in the cross-section areas is observed using Eurocode 3. For the considered steel cable net structure a weight saving of 17% for a partial factor for prestress 1.35 is obtained. If a partial factor for the prestress 1.0 could be considered, the weight reduction would be 4% more. Furthermore, the article investigates the effect of the partial factor for prestress (1.0 or 1.35), there prestress contributes to the stiffness in the non-lineair structural behaviour of membrane structures. The value of the partial factor for prestress to be considered is a source of disagreement between experts in different countries. With a similar geometry as the steel cable net structure, a membrane structure is designed and analysed. For the primary steel structure the partial factor for prestress 1.35 has to be applied. A 2% weight saving for the pretension factor 1.0 versus 1.35 is obtained if the tensile surface including the membrane and the edge cables is considered separate from the primary structure. A sound conclusion though requires a thorough in-depth study for different shapes and for different membrane types.